2014
DOI: 10.1016/j.ijsbe.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of bus and truck drivers affected from vehicle engine noise

Abstract: The purpose of this study was to find out the vulnerability of bus and truck drivers due to constant exposure of vehicle-engine noise inside the vehicle cabin. Comparative results revealed that noise levels inside the cabin of buses and trucks were in the range of 88.6-102.4 dB and 87.95-103.4 dB, respectively. The health status of bus and truck drivers was assessed by measuring their systolic and diastolic pressure, pulse rate, BMI, digestion problem, hearing loss, vision problem, back pain and irritation. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…A similar study by Mondal et al . [ 14 ] in West Bengal found that the noise level inside the buses’ cabin was in the range of 88.6–102.4 dB. Therefore, this study and similar studies indicate that the noise level inside the buses is well above the recommended standards.…”
Section: Discussionsupporting
confidence: 70%
“…A similar study by Mondal et al . [ 14 ] in West Bengal found that the noise level inside the buses’ cabin was in the range of 88.6–102.4 dB. Therefore, this study and similar studies indicate that the noise level inside the buses is well above the recommended standards.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, electrification enabling silent nighttime operation may reduce road congestion and increase transport efficiency (Pelletier, Jabali, & Laporte, 2018). Second, professional drivers often face adverse health effects such as partial hearing loss or stress-induced diseases (Guest et al, 2021;Karimi, Nasiri, Kazerooni, & Oliaei, 2010;Mondal, Dey, & Datta, 2014). The removal of ICE engines and increased transport efficiency may enable a reduction of these adverse impacts on drivers' well-being.…”
Section: Doctoral Processes and Project Contextmentioning
confidence: 99%
“…year, the level of the internal noise in the driver's space zone of 88.6÷102.4 dB was measured. As many as 65% of the surveyed drivers had been diagnosed with some the health problems caused by noise [6].…”
Section: Literature Rewiewmentioning
confidence: 99%